PERSEPSI DAN PARTISIPASI MASYARAKAT DALAM UPAYA REHABILITASI HUTAN DAN LAHAN DI KABUPATEN BOLAANG MONGONDOW TIMUR - Mamuko, Frida; Walangitan, H.; Tilaar, W. (Universitas Sam Ratulangi, 2016)
ABSTRAC The aim of this research are; to describe community perception and participation; analyze social and economy factors that influence perception and participation of community of the land and forest rehabilitation programme in East Bolaang Mongondow District. This research was conducted using survay analysis approach. Furthermore,analysis of perception and participation using Likert Scale. Survay was conducted to 102 respondents in 3 Sub Districts inculuding 7 villages in East Bolaang Mongondow District. The results of the research shows that perception level of respondents to the forrest and its function are 48% highly perception, medium perception 45.1 %, and 6.9 % low perception. Furthermore, perception level of respondents to the land and rehabilitation programme are 51% highly perception, medium perception 35%, and 10% respondents low perception. Rank Spearman Correlation analysis shows that perception level influenced by the education level. Â Analysis results of the participation level shows that 36.27 % highly perception, 34.31 % medium perception, and 29.41 % low perception. Rank Spearman Correlation analysis also shows that participation level influenced by the education level of the respondents. Keywords : perception, participation, land rehabilitation